Patients Regret Their Choice of Therapy Significantly Less Frequently after Robot-Assisted Radical Prostatectomy as Opposed to Open Radical Prostatectomy: Patient-Reported Results of the Multicenter Cross-Sectional IMPROVE Study - Wolff, Ingmar; Burchardt, Martin; Gilfrich, Christian; Peter, Julia; Baunacke, Martin; Thomas, Christian; Huber, Johannes; Gillitzer, Rolf; Sikic, Danijel; Fiebig, Christian; Steinestel, Julie; Schifano, Paola; et al. (Cancers, 2022)
Patient’s regret (PatR) concerning the choice of therapy represents a crucial endpoint for treatment evaluation after radical prostatectomy (RP) for prostate cancer (PCA). This study aims to compare PatR following robot-assisted (RARP) and open surgical approach (ORP). A survey comprising perioperative-functional criteria was sent to 1000 patients in 20 German centers at a median of 15 months after RP. Surgery-related items were collected from participating centers. To calculate PatR differences between approaches, a multivariate regressive base model (MVBM) was established incorporating surgical approach and demographic, center-specific, and tumor-specific criteria not primarily affected by surgical approach. An extended model (MVEM) was further adjusted by variables potentially affected by surgical approach. PatR was based on five validated questions ranging 0–100 (cutoff >15 defined as critical PatR). The response rate was 75.0%. After exclusion of patients with laparoscopic RP or stage M1b/c, the study cohort comprised 277/365 ORP/RARP patients. ORP/RARP patients had a median PatR of 15/10 (p < 0.001) and 46.2%/28.1% had a PatR >15, respectively (p < 0.001). Based on the MVBM, RARP patients showed PatR >15 relative 46.8% less frequently (p < 0.001). Consensual decision making regarding surgical approach independently reduced PatR. With the MVEM, the independent impact of both surgical approach and of consensual decision making was confirmed. This study involving centers of different care levels showed significantly lower PatR following RARP.
CRIS-Team Scopus Importer:2022-11-25
Keywords: characterization of patients; clinical decision-making; decision regret; prostate cancer; radical prostatectomy; survey